Front Cover: Scaffold Hopping from Amodiaquine to Novel Nurr1 Agonist Chemotypes via Microscale Analogue Libraries (ChemMedChem 8/2022). (20th April 2022) - Willems, Sabine; Müller, Marcel; Ohrndorf, Julia; Heering, Jan; Proschak, Ewgenij; Merk, Daniel
Abstract : The Front Cover shows a scaffold hop from amodiaquine to a new agonist of the neuroprotective transcription factor Nurr1 through library synthesis from rationally and computationally selected building blocks. The first library served to replace the diethylaminomethylphenol residue before the second set varied the chloroquinoline motif. The analogue libraries were prepared in microscale format in 1 mL glass tubes and tested for cellular Nurr1 activation after a simple workup. The most promising compounds of each library were synthesized in batch, isolated, and characterized to confirm Nurr1 agonism. Cover design by Sabine Willems. More information can be found in the Research Article by Sabine Willems, Marcel Müller, Daniel Merk et al.